Предмет: Алгебра,
автор: kisenisch
Упростить выражение
((sin^3альфа : cos альфа) + (cos^3(-альфа) : sin (-альфа))) + 4ctg2альфа) * tg 2 альфа
Ответы
Автор ответа:
0
заменим альфа на x(так писать удобней)
((sin^3x/cosx+cos^3(-x)/sin(-x))+4ctg2x)*tg2x=2
1). sin^3x/cosx+cos^3(-x)/sin(-x)=sin^3/cosx-cos^3/sinx=(sin^4x-cos^4x)/sinxcosx=
-(cos^2x-sin^2x)(sin^2x+cos^2x)/sinxcosx=-2cos2x/2sinxcosx(домножили на 2)=
-2cos2x/sin2x=-2ctg2x
2). -2ctg2x+4ctg2x=2ctg2x
3). 2ctg2x*tg2x=2cos2x/sin2x*sin2x/cos2x=2
Похожие вопросы
Предмет: География,
автор: tanya3896
Предмет: Физика,
автор: stasonych95
Предмет: Математика,
автор: moskovadara9
Предмет: Математика,
автор: Дяшка
Предмет: Алгебра,
автор: kseniya123